OPTIMALISASI STRATEGI DIGITAL MARKETING DALAM MENINGKATKAN BRAND AWARENESS BRI INSURANCE - Koentoro, Anton Topo; Amrita, Nyowan Dwika Ayu (Jurnal MBE Manajemen Bisnis, Equilibrium, 2025)
Digital marketing strategy plays a crucial role in enhancing brand awareness, especially in the insurance industry, which faces unique challenges in building emotional relationships with consumers. As one of the leading insurance companies in Indonesia, BRI Insurance needs to optimize its digital marketing strategy to compete effectively in the digital landscape. This study aims to evaluate and analyze the most optimal digital marketing strategies for improving BRI Insurance's brand awareness. The research method used is a literature study based on 21 relevant scholarly articles published in the last five years. The results show that an integrated digital approach involving social media, content marketing, SEO, and influencer collaboration significantly increases brand awareness.